Compressive Strength of Tubular Members with Combined Pitting Corrosion and Crack Damage - Wang, Ren-hua; Wang, Zhi-wen (China ocean engineering, 2023)
Tubular members subject to combined pitting corrosion and crack damage were numerically studied to clarify the reduction of ultimate strength and failure behavior, based on numerical models validated against available experiments. The effects of length, location and inclined angle of a crack under combined damage were studied to disclose the mechanism of interaction between the crack and corrosion pits. The methods, named as linear superposition directly accumulating the effects of solo crack and solo pitting damage, as well as crack projection transferring an inclined crack to a transverse one, were discussed and verified in the view of assessing ultimate strength of tubular members with combined damage. It was shown that the former is practical but complex while the next always overestimates the residual strength. Besides, the location and inclined angle of a crack have a subtle effect on the reduction of ultimate strength under combined damage, especially at higher level of pitting damage, due to the synergistic effect between corrosion pits and cracks. Such effect can lead to early occurrence of plasticity and local buckling by inducing stress interaction between crack tips and pits, and causing more significant strength reduction compared with a solo type of damage. A practical method was proposed to determine the loss ratio of cross-sectional area on the equivalent weakest section of a damaged member. Based on the loss ratio, a formula was presented to predict the ultimate strength of damaged members with combined damage, showing good applicability.